The Influence of Words of Mouth and Sapta Pesona on the Decision to Visit Natsepa Beach - Tri Djoko Sulistio; Rina Fitriana; Leinda Melisa (Institute of Computer Science (IOCS), 2021)
This study aims to determine the influence of Words of Mouth and Sapta Pesona (in English: seven enchantments) on the decision to visit Natsepa Beach in Central Maluku. This is quantitative descriptive research that uses the simple random sampling to gather the data. The sample consists of 100 visitors of the beach and is taken using Slovin formula with the margin of error of 10%. The testing use in this research are validity test, reliability test, while the data analysis technique uses descriptive statistical test, correlation coefficient test, simple linear regression test, multiple linear regression test, T test, F test, and test coefficient of determination. The result shows that there is a relationship and influence of the Words of Mouth and Sapta Pesona on the visitors’ decision to Visit Natsepa Beach by 78.2% meanwhile other influencing factors that are not found out in this research.